A Linguistic Analysis of Selected Verses in Surat Joseph - Bajri, Ibtesam AbdulAziz (Advances in Social Sciences Research Journal, 2017)
There is more beyond what we could readily hear and see but also about our perceptions about signs and wonders and mental images that correspond to some distinct entities, or to its essential features thus playing an important part in the use of reason or language. This article deals with written messages in the form of verses from the Holy Qur'an. To be specific, we have chosen some verses in Surat Joseph with prevalent usage of signs to accomplish its ends. Under the tradition of Peircean model, semiotic application is broader and fundamental. Given that the Story of Joseph is widely read and reinterpreted several times, we have offered and injected some fresh revelations as spiritually discerned during our research. Any slight variations in/by the ‘interpretant’ are treated as a welcome development as in all fields of endeavors that further give richness and beauty dependent on cultures, social and geographical diversities. We adhere to the idea that variety is the spice of live, that we have come to learn and accept our differences. However, consistencies are relevant and warranted in areas where interpretation of the attributes of our Creator Allah is concerned – His unlimited love for mankind reigns supreme. Key Words: Semiotics; sign; Peircean model; representamen; interpretant; object